2018
DOI: 10.13057/biodiv/d190214
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of aboveground C-stock between cacao-based agroforestry system and cacao monoculture practice in West Sumatra, Indonesia

Abstract: Santhyami, Basukriadi A, Patria MP, Abdulhadi R. 2018. The comparison of aboveground C-stock between cacao-based agroforestry system and cacao monoculture practice in West Sumatra, Indonesia. Biodiversitas 19: 472-479. One of the main cause of climate change is deforestation for agricultural purposes. Therefore, Agroforestry System-AFS is regarded as a benign approach to reduce pressure on natural forest while still meeting the needs of local communities. In West Sumatra, Indonesia, small-scale AFS with cacao … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
1
9
1
Order By: Relevance
“…Our results are different from those of Santhyami et al (2018), where total aboveground C-stock in biomass was six to ten times higher in the cacao-based agroforestry than in monoculture cacao. This difference is due to differences in undergrowth species in monoculture and agroforestry systems.…”
Section: Understorey Plant Carboncontrasting
confidence: 99%
“…Our results are different from those of Santhyami et al (2018), where total aboveground C-stock in biomass was six to ten times higher in the cacao-based agroforestry than in monoculture cacao. This difference is due to differences in undergrowth species in monoculture and agroforestry systems.…”
Section: Understorey Plant Carboncontrasting
confidence: 99%
“…This has a direct impact on stored biomass. Many studies in the tropics have shown similar results, such as in Cameroon [59] and Indonesia [60].…”
Section: Structure Of Cocoa Agroforestssupporting
confidence: 63%
“…In Mindanao, the Philippines, Tolentino et al (2010) found that complex agroforestry systems had a carbon stock of 192 t C ha -1 , which is three times more than the carbon stock of tree plantations (59 t C ha -1) . Multi-strata cacao-agroforestry systems in Indonesia and the Philippines have been shown to hold stock above 100 t C ha -1 for aboveground carbon (Lasco et al 2001, Santhyami et al 2018. If agroforestry systems in Viet Nam were expanded to their potential of an additional 10 million ha, at least 260 Mt C could be sequestered annually (Mulia et al 2018(Mulia et al , 2020.…”
Section: Systemmentioning
confidence: 99%